ANALISIS TINGKAT INFLASI, DANA PIHAK KETIGA, SUKU BUNGA, NILAI TUKAR DAN PRODUK DOMESTIK BRUTO TERHADAP PERMINTAAN KREDIT PADA BANK UMUM DI INDONESIA - wulandari, ririn (Jurnal Pembangunan dan Pemerataan, 2021)
A bank is an institution that collects funds from people who have excess funds and channel these funds back to people who need them on credit. Banking policy that can stimulate economic growth is the demand for credit. Providing credit to producer communities is expected to increase the amount of capital which will later expand the business which will have an impact on economic growth. The demand for credit in general has increased from year to year, considering that the need for money has also increased, demand for credit is the total credit extended by commercial banks including consumer, working capital and investment loans. This study uses a descriptive method with secondary data available at Bank Indonesia and OJK. In addition, for testing and calculating the research data, the researcher uses the classical assumption test and the VAR model. The conclusions from the results of this study indicate that the inflation variable has a significant effect on demand for credit, the TPF variable has no significant effect on credit demand, the interest rate variable has no significant effect on credit demand, the exchange rate variable has no significant effect on credit demand. GDP has an insignificant negative effect on Credit Demand.Keywords: Credit Demand, Inflation, Commercial Banks.